Between Permit and Title: Legal Reconstruction of Apartment Ownership and Licensing Systems - Syamsuddin, Zaki Achmad; Khairunnisa, Salsabila Shafa (Indonesian Journal of Agrarian Law, 2024)
The dispute between residents and the management of the Solo Paragon Apartment demonstrates that legal protection for consumers in vertical housing is ineffective. This study aims to analyze the forms of legal protection available to apartment residents as consumers in the face of management's actions that restrict access to shared facilities. This study uses a normative juridical approach, using a case study of the dispute at the Solo Paragon Apartment. The results indicate that the management's actions are inconsistent with Law Number 8 of 1999 concerning Consumer Protection and the Government Regulation on Apartments. The court ruling stated that the management had committed an unlawful act, and residents are entitled to restored access to facilities. The study concludes that there is a need to strengthen regulations and oversight in apartment management to ensure legal protection for consumers. This protection must be active and comprehensive, both in terms of prevention and enforcement of violations. This case serves as a clear example of the weakness of consumer protection in apartment management practices and the importance of regulatory reform and legal assistance for consumers.